Grief experiences of nurses after the death of an adult patient in an acute hospital setting: An integrative review of literature. Issue 2 (April 2019) - Meller, Nikki; Parker, Deborah; Hatcher, Deborah; Sheehan, Athena
Abstract: Objective: This integrative review explores current published literature examining grief experiences of nurses who work in hospital settings after the death of a patient in their care and the factors that may impact nurses experiencing grief within the workplace. Background: Healthcare workers such as nurses are required to be competent, skilled and resilient in preparation for the emotional variables and professional responsibilities when managing a patient death. There are publications exploring nurse's grief experiences in palliative care, paediatric nursing or oncology settings, but to date, there is limited relevant literature identifying or exploring grief experiences of nurses working in other speciality areas in a hospital setting after the death of a patient in their care. Methods: Comprehensive online database searches of CINAHL, EBSCO Host, PubMED, MEDLINE, Scopus, Joanna Briggs Institute (JBI) and Google Scholar was undertaken using key terms of articles published between 1990–2017. Screening of 317 articles resulted in 5 included for this review. Data analysis was guided by Whittemore and Knafl's five stage process. Findings: Three main themes were identified were 'the impact of formative death events in clinical practice', 'managing personal grief reactions and the factors that influenced these reactions', and 'the significance of colleague support when experiencing a patient death'. Conclusion: Personal grief responses displayed by a nurse after a patient has died can have both a positive and negative influence on their professional behaviour in the workplace. It also has the potential for grief complications for individual nurses, which highlights the importance of workplace support for nurses when making clinical decisions after the death of a patient.